1971
DOI: 10.1901/jeab.1971.16-189
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Movement and Real Movement Detection in the Pigeon: Stimulus Generalization

Abstract: Pigeons were trained to discriminate apparent movement Siegel (1970) suggested that pigeons can also detect lines in apparent movement (AM) over a wide range of directions. The mechanism of directional detection is unknown, although directional specific cells have been found in the pigeon retinae (Maturana and Frenk, 1963) and the optic tectum (Wylie, 1962). While it has been speculated that perception of real movement and apparent movement are derived from the same basic electrophysiological process (Aaron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1

Year Published

1973
1973
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
0
10
1
Order By: Relevance
“…Note that this is apparent motion rather than real motion, since there is no actual motion within each 3-mm bar. Nevertheless, the motion is convincing to the human eye; moreover, Siegel (1971) has shown strong equivalence between real and apparent motion in pigeons, using apparent motion displays of considerably coarser "grain" than those of the present study.…”
Section: Apparatuscontrasting
confidence: 42%
See 1 more Smart Citation
“…Note that this is apparent motion rather than real motion, since there is no actual motion within each 3-mm bar. Nevertheless, the motion is convincing to the human eye; moreover, Siegel (1971) has shown strong equivalence between real and apparent motion in pigeons, using apparent motion displays of considerably coarser "grain" than those of the present study.…”
Section: Apparatuscontrasting
confidence: 42%
“…In any case, for those birds which participated in both phases of the experiment, the discrimination phase actually preceded the nystagmus phase. It is, of course, conceivable that the discrimination procedure was somehow too insensitive to reveal subtle perceptual effects, or that apparent movement is perceived differently from real movement (despite Siegel's, 1971, evidence to the contrary), or that other parameters, such as distance, speed, or spatial frequency, crucially determine whether there is asymmetry or not. We think it more likely that the mechanisms underlying the asymmetry in the nystagmus response are simply quite separate from those involved in discrimination learning.…”
Section: Discussionmentioning
confidence: 99%
“…Since we know that pigeons are able to see not only real movement, but also apparent movement, like the phi-phenomenon (Siegel, 1970(Siegel, , 1971Emmerton, 1990), we plan to use Stroboscopic Alternative Movement (SAM) as the reference pattern. If it is true that self-organization processes also occur in animal cognition, then there should also be multistability.…”
Section: Discussionmentioning
confidence: 99%
“…Movement thresholds have been measured in humans (Brown, 1931), chimpanzees (Carpenter & Carpenter, 1958), cats (Kennedy & Smith, 1935), rats (Hawley & Munn, 1933), and pigeons (Hodos et al, 1976;Siegel, 1970Siegel, , 1971. Siegel (1970Siegel ( , 1971 demonstrated that pigeons can discriminate between stationary (nonmoving) stimuli and stimuli presented as real or apparent movement.…”
mentioning
confidence: 99%
“…Siegel (1970Siegel ( , 1971 demonstrated that pigeons can discriminate between stationary (nonmoving) stimuli and stimuli presented as real or apparent movement. Hodos et al (1976) I wish to thank Coleman Paul for his contributions trained pigeons to discriminate between stationary and dynamic stimuli.…”
mentioning
confidence: 99%